2022
DOI: 10.5826/dpc.1204a176
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Dermoscopy in the Delineation of Basal Cell Carcinoma for Mohs Micrographic Surgery

Abstract: Introduction: Several studies investigated the use of dermoscopy in the delineation of Basal cell carcinoma (BCC) for Mohs micrographic surgery (MMS) with conflicting results Objective: The purpose of this systematic review with meta-analysis was to evaluate the effectiveness of the use of dermoscopy-guided MMS in the treatment of BCC. Methods: We included all comparative studies including more than twenty-five cases. Cases of BCC treated using dermoscopy-guided MMS (or slow MMS) were compared to those treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A recent systematic review demonstrated that there was no statistically significant difference in the proportion of total margin clearance on the first MMS stage between basal cell carcinomas removed using dermoscopy-guided MMS and those that had curettage or visual inspection. 19 Despite the mixed evidence for the role of dermoscopy in MMS, we believe that dermoscopy helps with lateral tumor delineation and biopsy site identification.…”
Section: Discussionmentioning
confidence: 77%
“…A recent systematic review demonstrated that there was no statistically significant difference in the proportion of total margin clearance on the first MMS stage between basal cell carcinomas removed using dermoscopy-guided MMS and those that had curettage or visual inspection. 19 Despite the mixed evidence for the role of dermoscopy in MMS, we believe that dermoscopy helps with lateral tumor delineation and biopsy site identification.…”
Section: Discussionmentioning
confidence: 77%
“…Theoretically, dermoscopic examination would allow for more accurate initial margin mapping, allowing for a decrease in incidental findings, fewer Mohs layers, and narrower overall excision size. In 2022, Litaiem and colleagues 10 conducted a systematic review and meta-analysis, which compared dermoscopic examination before Mohs surgery with curettage and preoperative visual inspection. The authors found mixed results with lateral margin clearance being greater, but no difference in total margin clearance after the first MMS stage in the dermoscopy group as compared with the control groups (curettage and visual inspection).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, dermoscopy revealed no statistically significant differences in the proportion of complete margin clearance on the first MMS stage between BCCs treated with dermoscopy-guided MMS and those who underwent curettage or visual inspection. However, lateral margin involvement was significantly lower in BCCs that had dermoscopy-guided MMS [ 22 ].…”
Section: Discussionmentioning
confidence: 99%